The Relationship Between Sleep Quality and Cognitive Function in The Elderly at The Tresna Werdha Social Institution - Hanum, Hilda Tiara; Pudjiati, Pudjiati; Maryam, Raden Siti; Badriah, Siti; Resnayati, Yeti (Journal of Nursing Care, 2025)
Background: Cognitive changes in the elderly are a natural consequence of the degenerative process. In this process, sleep quality becomes an important factor affecting cognitive function. While it is known that prolonged sleep disturbances can increase the risk of cognitive impairment in the elderly, few studies have specifically explored the relationship between sleep quality and cognitive function in the context of the elderly in elderly residents. Aim: To determine the relationship between sleep quality and cognitive function in elderly residents. Methods: This study used a quantitative method with a descriptive-analytic design and a cross-sectional approach. The research population comprised all elderly residents of Tresna Werdha Social Institution Budi Mulia 3 in Jakarta, totaling 282 individuals, with a sample size of 80 elderly individuals selected using simple random sampling. Data collection was conducted using questionnaires, and data analysis was performed using the Chi-square test. Results: The results showed that the majority had good sleep quality (55%) and normal cognitive function (51.2%). There is a significant relationship between sleep quality and cognitive function (p=0.000) with an OR value of 19.444. Conclusion: There is a significant relationship between sleep quality and cognitive function in the elderly. Recommendations: Based on the results of this study, it is recommended that nurses carry out community-based interventions, such as sleep health education activities and stress management, to support comprehensive elderly health. Further research is recommended to develop and test the effectiveness of non-pharmacological-based interventions, such as cognitive behavioural therapy and meditation techniques, in improving the quality of elderly sleep. Keywords: cognitive function; elderly; sleep quality.